Motivating factors to promote tourism in India: using AHP methods. Issue 3 (7th July 2022) - Kumar, Rupesh; Kansara, Surendra; Bangwal, Deepak; Damodaran, Akhil; Jha, Ajay
This study seeks to investigate the various criteria along with different motivation factors with the motive to improve people's leisure time. All these motivating factors have their importance to enhance tourism within the country and also help in economic development. The primary data of this research collected through a questionnaire survey. Then we used the analytic hierarchy process (AHP) theory to analyse the factors and sub-factors of the hierarchical structure. This study reveals the application of AHP to examine the tourism theory and suggested recommendations and solutions for the Indian tourism industry. The proposed framework can be used by tour operators to avoid the uncertainty in decision making as well to improve the efficiency of tourism performance.